Structuring and Sharing Information Resources to Support Concept Development and Design Learning - Grierson, Hilary; Nicol, David; Littlejohn, Allison; Wodehouse, Andrew (Proceedings of the International Conference on Networked Learning, 2004)
This study investigates how a shared workspace and digital repository might help student teams share information and resources while learning to design. An open-source groupware product called TikiWiki was configured so that teams could structure their design resources using wiki pages (like web pages) and share them using two search strategies – browsing the wiki pages or using keywords. The results showed that the structuring of information supported learning and that teams preferred to search the wiki structures rather than use keywords. The discussion focuses on students’ search strategies and ways that metadata that might improve resource sharing across teams.